Nanoparticles for Stem Cell Therapy Bioengineering in Glioma - Ruiz-Garcia, Henry; Alvarado-Estrada, Keila; Krishnan, Sunil; Quinones-Hinojosa, Alfredo; Trifiletti, Daniel M. (Frontiers in Bioengineering and Biotechnology, 2020)
Gliomas are a dismal disease associated with poor survival and high morbidity. Current standard treatments have reached a therapeutic plateau even after combining maximal safe resection, radiation and chemotherapy. In this setting, stem cells (SC) have risen as a promising approach given their intrinsic tumor homing as well as their natural or bioengineered antitumor properties. The interplay between stem cells and other therapeutic approaches such as nanomedicine holds the potential to synergize the advantages of the combine therapeutic strategies. Nanoparticles represent a broad spectrum of synthetic and natural biomaterials that have been proven effective in expanding diagnostic and therapeutic efforts either used alone or in combination with immune, genetic or cellular therapies. Stem cells have been modified using these biomaterials to enhance their natural antitumor properties as well as to act as their vehicle when intrinsic anticancer biomaterials need to be delivered to tumor regions. We will present here the recent developments of this new paradigm in the treatment of malignant gliomas.